Output volatility and openness to trade: A reassessment - Eduardo A. Cavallo (Inter-American Development Bank, Research Department, 2007)
Many economists believe that, while openness to trade increases average GDP growth rates, it also raises output volatility by exposing countries to terms-oftrade shocks. This view does not take into account that, as suggested by a recent strand of the financial fragility literature, commercial trade might also reduce financially related volatility. Once this is taken into account, the relationship between exposure to trade and output volatility is still an open question. Trade therefore is not necessarily a destabilizing force in countries that are exposed to volatile capital flows. This paper presents new empirical evidence that suggests that the net effect of trade openness on output volatility is stabilizing. The methodology employed seeks to correct for the likely endogeneity of trade in this setting using gravity estimates as instrumental variables. The results confirm that exposure to trade raises output volatility through the terms-of-trade channel, as previously documented in the literature, but also shows that this is counteracted by a quantitatively larger stabilizing effect. Additional evidence is presented showing that the latter effect comes (at least in part) through the financial channel. Splitting the sample into countries that are more exposed to capital flows and countries that are less exposed, the paper shows that the stabilizing effect of commercial trade predominates in the first sub-sample.
Keywords: F36; F40; 330; openness to trade; output volatility; financial crises; gravity equation; Wirtschaftswachstum; Außenhandelsliberalisierung; Terms of Trade; Schock; Gravitationsmodell; Theorie; Welt